Precarity and preparedness during the SARS‐CoV‐2 pandemic: A qualitative service evaluation of maternity healthcare professionals - Kaat De Backer; Jeremy M. Brown; Abigail Easter; Nina Khazaezadeh; Daghni Rajasingam; Jane Sandall; Laura A. Magee; Sergio A. Silverio (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The SARS‐CoV‐2 pandemic has devastated populations, posing unprecedented challenges for healthcare services, staff and service‐users. In the UK, rapid reconfiguration of maternity healthcare service provision changed the landscape of antenatal, intrapartum and postnatal care. This study aimed to explore the experiences of maternity services staff who provided maternity care during the SARS‐CoV‐2 pandemic to inform future improvements in care. Material and methods A qualitative interview service evaluation was undertaken at a single maternity service in an NHS Trust, South London. Respondents (n = 29) were recruited using a critical case purposeful sample of maternity services staff. Interviews were conducted using video‐conferencing software, and were transcribed and analyzed using Grounded Theory Analysis appropriate for cross‐disciplinary health research. The focus of analysis was on staff experiences of delivering maternity services and care during the SARS‐CoV‐2 pandemic. Results A theory of “Precarity and Preparedness” was developed, comprising three main emergent themes: “Endemic precarity: A health system under pressure”; “A top‐down approach to managing the health system shock”; and “From un(der)‐prepared to future flourishing”. Conclusions Maternity services in the UK were under significant strain and were inherently precarious. This was exacerbated by the SARS‐CoV‐2 pandemic, which saw further disruption to service provision, fragmentation of care and pre‐existing staff shortages. Positive changes are required to improve staff retention and team cohesion, and ensure patient‐centered care remains at the heart of maternity care.